THE INFLUENCE OF MOTIVATION, DISCIPLINE, AND WORK COMPETENCE ON EMPLOYEE PERFORMANCE AT THE BAWASLU SECRETARIAT OF NORTH SUMATRA PROVINCE - Elisa Rusmayanti Sianturi; Sapta Pratama Sembiring; Melia Putri; Mila Yulia Herosian; Dwita Sakuntala (CV. Radja Publika, 2026)
This study aims to determine and analyze the influence of motivation, discipline and work competence on employee performance at the Secretariat of BAWASLU of North Sumatra Province. This type of research uses quantitative research. The research sample was 85 respondents. The data analysis method used multiple linear regression analysis. Based on the results of the t hypothesis test, it can be concluded that motivation has a significant effect on employee performance with a calculated tvalue of 3.313>ttable 1.990 and a significance value of 0.001<0.05, discipline has a significant effect on employee performance with a calculated tvalue of 3.835>ttable 1.990 and a significance value of 0.000<0.05 and competence has a significant effect on employee performance with a calculated tvalue of 3.01>ttable 1.990 and a significance value of 0.003<0.05. Based on the results of the F hypothesis test, it can be concluded that motivation, discipline, and competence simultaneously influence employee performance, with an Fvalue of 38.098 > ttable 2.720 and a significance value of 0.000 <0.05. Based on the coefficient of determination analysis, the coefficient of determination or Adjusted R-Square was obtained at 0.570, or 57% of motivation, discipline, and competence influence employee performance, while 43% is the influence of other variables not included in this study.